Organizational communication satisfaction as a moderator between the big five personality traits and job satisfaction among employees in Nigeria - Jarrar, Yosra; Ammar, Lujain; Nweke, Gabriel; Horoub, Ibrahim; Aderibigbe, Adebola (Frontiers in Psychology, 2025)
This study focuses on understanding the relationship between job satisfaction and the big five personality traits: openness, conscientiousness, extroversion, agreeableness, and neuroticism, with the moderation of organizational communication. Taking into consideration the recent evaluation of traits within employees in the workplace, both within the positive and negative notions, this study aims to further explore the effect of the major five personality traits to help better understand which could boost and strengthen the workplace society in recent times, where wellbeing is fluctuating. The study uses the convenience sampling technique on employees of Bowen University in Nigeria to discover the relationship between job satisfaction and the big five personality traits with organizational communication as the moderator. The independent variables of the study are personality traits: openness, conscientiousness, extroversion, agreeableness, and neuroticism while the dependent variable is job satisfaction, and the organizational communication satisfaction will serve as the moderator variable. The study's findings showed a positive relationship between job satisfaction and openness, conscientiousness, extroversion, and agreeableness, however, discovered a negative relationship between job satisfaction and neuroticism. In addition, the study found a positive relationship between organizational communication satisfaction and job satisfaction. As a moderator, the findings presented a positive role of organizational communication satisfaction in moderating the connection between openness, extroversion, agreeableness, and neuroticism with job satisfaction, but was not supported within its moderating between openness and job satisfaction, as well as within conscientiousness and job satisfaction. The study overall confirmed the effect of the big five personality traits on job satisfaction with connection to organizational communication satisfaction.